Assessment of oral health parameters among students attending special schools of Mangalore city - Tom Peter; Deepthi Anna Cherian; Tim Peter (Wolters Kluwer Medknow Publications, 2017)
Background: The aim of the study was to assess the oral health status and treatment needs and correlation between dental caries susceptibility and salivary pH, buffering capacity and total antioxidant capacity among students attending special schools of Mangalore city. Materials and Methods: In this study 361 subjects in the age range of 12-18 years were divided into normal (n = 84), physically challenged (n = 68), and mentally challenged (n = 209) groups. Their oral health status and treatment needs were recorded using the modified WHO oral health assessment proforma. Saliva was collected to estimate the salivary parameters. Statistical analysis was done using Statistical Package for Social Sciences version 17. Chicago. Results: On examining, the dentition status of the study subjects, the mean number of decayed teeth was 1.57 for the normal, 2.54 for the physically challenged and 4.41 for the mentally challenged study subjects. These results were highly statistically significant (P < 0.001). The treatment needs of the study subjects revealed that the mean number of teeth requiring pulp care and restoration were 1 for the normal, 0.12 for the physically challenged, and 1.21 for the mentally challenged study subjects. These results were highly statistically significant (P < 0.001). The mean salivary pH and buffering capacity were found to be lowest among the mentally challenged subjects. Physically challenged group had the lowest mean total antioxidant capacity among the study subjects. Among the study subjects, normal students had the highest mean salivary pH, buffering capacity, and total antioxidant capacity. These results were highly statistically significant (P < 0.001). Conclusion: This better dentition status of the normal compared to the physically and mentally challenged study subjects could be due to their improved quality of oral health practices. The difference in the treatment needs could be due to the higher prevalence of untreated dental caries and also due to the neglected oral health care among the mentally challenged study subjects. The salivary pH and buffering capacity were comparatively lower among the physically and mentally challenged study subjects which could contribute to their increased caries experience compared to the normal study subjects. However, further studies are needed to establish a more conclusive result on the total anti-oxidant capacity of the saliva and dental caries.